Metabolic and Morphological Aspects of Adaptation of Alkaliphilic Bacillus aequororis 5-DB and Alkali-Tolerant Bacillus subtilis ATCC 6633 to Changes in pH and Mineralization - Yuliya Maksimova; Ann Eliseeva; Aleksandr Maksimov (International Journal of Microbiology)
The goal of the study is to evaluate metabolic and morphological changes of the facultative alkaliphile Bacillus aequororis 5-DB and the weakly alkali-resistant B. subtilis ATCC 6633 in a wide pH range and at different NaCl concentrations. The alkaliphile B. aequororis 5-DB is shown to have a broader general resistance to adverse factors (wide pH range, 50 g/L NaCl) than a weakly alkali-tolerant strain of the same genus. This alkaliphile is also shown to have a significantly greater resistance not only to high pH but also to low pH in comparison with B. subtilis ATCC 6633. The resistance of B. aequororis 5-DB to low pH was expressed in higher metabolic activity, maintenance of ΔpH, and no significant cell damage. The selected set of methods (reduction of resazurin to resorufin by cell dehydrogenases, bioluminescent method for determining ATP, AFM, and measurement of intracellular pH) allows us to adequately assess the ability of microbial cells to withstand harsh environmental factors. Nonspecific resistance of B. aequororis 5-DB was proven using a complex of selected methods. Tolerance to a wide range of pH and high salt concentrations may be useful for biotechnological applications of the strain.